The legal development of the notion of human dignity in the constitutional jurisprudence/ O desenvolvimento legal da noção de dignidade humana na jurisprudência constitucional - Staffen, Marcio Ricardo; Arshakyan, Mher (Revista Brasileira de Direito, 2016)
ABSTRACT: The present paper, based on a comparative method, aims to analyze the dimension given by the constitutional courts of the United States of America, Germany, South Africa, Israel, France, Canada and Brazil, as well as in the regional systems of protection of Human Rights With respect to the concept and extension of the principle of the dignity of the human person, establishing approximations and critical analyzes on philosophical aspects that permeate its birth and its cultural, individual and jurisprudential assimilations. Finally, it is concluded that while dignity-based reputation is a universal virtue, its content largely depends on the social, religious, and traditional values of certain communities.KEYWORDS: Dignity. Judicial Interpretation. Concept. RESUMO: O presente artigo científico, partindo de método comparado, objetiva analisar a dimensão dada pelas cortes constitucionais dos Estados Unidos da América, Alemanha, África do Sul, Israel, França, Canadá e Brasil, bem como nos sistemas regionais de tutela dos Direitos Humanos no que diz respeito ao conceito e à extensão do princípio da dignidade da pessoa humana, estabelecendo aproximações e análises críticas sobre aspectos filosóficos que permeiam seu nascedouro e suas assimilações culturais, individuais e jurisprudenciais. Por fim, conclui-se que enquanto a reputação baseada na dignidade for uma virtude universal, seu conteúdo depende largamente de valores sociais, religiosos e tradicionais de certas comunidades.PALAVRAS-CHAVES: Dignidade. Interpretação judicial. Conceito.